Pajak Penghasilan dan Keputusan Pendanaan (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Purnamasari, Yenny (Jurnal Akuntansi Kontemporer, 2009)
This research has a purpose to provide empirical testing about influencing of income tax which is used as management consideration to make financial decisions. The examined factors on this research are tax and non tax factors, leverage policy, and dividend policy. The sample consist of 32 manufacturing companies, which are listing in Indonesian Capital Market, is chosen by purposive sampling. Moreover the statistic method used to test on the research hypothesis is Multivariate Multiple Regressions. The results show that income tax is one of the consideration management factors for making good financial decisions. The results also proved that leverage and dividend policy are significantly influenced by income tax.